Identification and monitoring of Saharan dust: An inventory representative for south Germany since 1997. (May 2015) - Flentje, H.; Briel, B.; Beck, C.; Collaud Coen, M.; Fricke, M.; Cyrys, J.; Gu, J.; Pitz, M.; Thomas, W.
Abstract: An inventory of Sahara dust (SD) events at the Hohenpeiβenberg Global Atmosphere Watch station (Germany) is presented for the period 1997–2013. Based on daily in-situ measurements, high Ca 2+ -ion concentrations and large particle volume concentrations at diameters d p  ≈ 0.5–7 μm are inferred as indicators for days influenced by SD. The resulting SD catalogue agrees with SD time series from Schneefernerhaus, Augsburg and Jungfraujoch stations. On average, SD occurs in 5–15 SD events (SDE) per year covering about 10–60 days/yr in the mixing layer. SDE exhibit a clear seasonality with spring and early autumn maxima, and typically last for 1–3 days. SDE are equally frequent but more significant at Alpine levels due to lower background. Wet deposition of Ca 2+ at the surface is little correlated (R 2  = 0.14) with particle Ca 2+ on a daily basis and yields an average annual Ca 2+ immission of 0.22 ± 0.04 g/m 2  yr, about 40% of which is due to SD. The majority of outstanding weekly Fe and Al depositions are associated with SDE. SD contributes about 0.5 ± 0.1 μg/m 3 to the total particle mass with a decreasing trend from 6% to 4% (−0.1%/yr) in the 1997–2013 period. Except from one, all threshold exceedances according to European legislation (daily PM10  > 50 μg/m 3 ) at Hohenpeiβenberg are due to SD. Implications are discussed with respect to SD-related circulation patterns, SD-induced temperature anomalies in weather forecast models and the capability of aerosol models to capture SDE. Highlights: Large Ca 2+ abundance and coarse particle volume (0.5–7 μm) indicate Saharan dust. The annual number of Saharan dust days shows no significant trend. The relative contribution of dust to total particle mass decreases from 6% to 4%. Sahara dust events, detected by different metrics at different stations, are consistent. 4 of 5 EU law threshold exceedances (daily PM10 > 50 mg/m 3 ) are due to Saharan dust.